2020
DOI: 10.3390/pharmacy8020083
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Development of Therapeutic-Decision-Making Skills by Practicing Pharmacists Undertaking a University-Based Postgraduate Clinical Qualification at Distance

Abstract: (1) Background: The processes and skills required to make decisions about drug therapy have been termed “therapeutic decision-making” in pharmacy practice. The aim of this study was to evaluate a tool constructed to measure the development of therapeutic-decision-making skills by practicing pharmacists undertaking a university-based continuing professional development program. (2) Methods: A pre- and post-intervention crossover study design was used to investigate the qualitative and quantitative features of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Some studies focused on dispensing and communication skills development [ 12 , 31 , 41 , 42 , 43 ], while others focused on the assessment of the knowledge, metacognition support, and promoting active learning, student confidence and independent studying [ 4 , 11 , 13 , 15 , 16 , 28 , 33 , 35 , 36 , 37 , 40 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Some literature focused more on presenting the CBS platform and students’ perceptions of it [ 34 , 38 , 39 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies focused on dispensing and communication skills development [ 12 , 31 , 41 , 42 , 43 ], while others focused on the assessment of the knowledge, metacognition support, and promoting active learning, student confidence and independent studying [ 4 , 11 , 13 , 15 , 16 , 28 , 33 , 35 , 36 , 37 , 40 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Some literature focused more on presenting the CBS platform and students’ perceptions of it [ 34 , 38 , 39 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review included 46 pieces of literature; 41 studies from standard literature (89.1%: T1), one commentary [ 4 ], and four grey literature reports [ 2 , 18 , 63 , 64 ]. The included studies had a broad global representation; 46.3% ( n = 19) of the standard literature studies were undertaken in the USA [ 5 , 6 , 7 , 12 , 39 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], followed by Australia (19.5%, n = 8) [ 3 , 4 , 28 , 79 , 80 , 81 , 82 , 83 ], then the UK ( n = 4) [ 8 , 42 , 84 , 85 ], New Zealand ( n = 2) [ 86 , 87 ], Canada ( n = 2) [ 88 , 89 ], Brazil ( n = 1), Sweden ( n = 1) [ 9 ], Portugal ( n = 1) [ 90 ], the Netherlands ( n = 1) [ 91 ], and three studies that included participants from different countries (one in Australia and Malaysia [ 92 ], and the other for multiple European country graduates [ 35 ,…”
Section: Resultsmentioning
confidence: 99%
“…In some of those studies, it was reported that students were found to be skeptical about using CBS based on previous experience, misconceptions, or fears that such a training method would hinder their training quality. This pre- judgment among students may have affected their confidence in CBS [ 6 , 7 , 8 , 12 , 28 , 35 , 66 , 71 , 72 , 77 , 78 , 79 , 82 , 87 , 97 ], especially if they experienced system errors and/or technical difficulties [ 6 , 8 , 28 , 77 , 79 ]. Moreover, it was reported that some students might prefer the traditional method rather than adopting a new learning method [ 6 , 7 , 12 , 35 , 71 , 72 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 Embedded within the PPCP are the steps of therapeutic decision making: gather information (collect), appraise the data (assess), make recommendations including by analyzing benefits and risks of different treatment options (plan), and enact and monitor the decision (implement and follow-up). [1][2][3][4] However, this is a general process applicable across practice settings and it does not provide detailed guidance about what information is critical to collect and assess prior to making an OTC recommendation. 5 Given there are more than 300,000 OTC medications marketed in the United States, including products in more than 80 therapeutic classes, it is critical that student pharmacists learn how to make patientcentered OTC medication recommendations.…”
Section: Description Of the Problemmentioning
confidence: 99%